Catalytic pyrolysis of poplar wood over transition metal oxides: Correlation of catalytic behaviors with physiochemical properties of the oxides. (May 2019) - Zhang, ChenTing; Zhang, Lijun; Li, Qingyin; Wang, Yi; Liu, Qing; Wei, Tao; Dong, Dehua; Salavati, Saman; Gholizadeh, Mortaza; Hu, Xun
Abstract: Metal oxides are frequently used in the formulations of the catalysts for catalytic pyrolysis of biomass. This study aims to investigate the catalytic behaviors of the transition metal oxides (CoO, Cr2 O3, CuO, Fe2 O3, Mn2 O3, NiO, TiO2 and V2 O5 ) as well as CeO2 for the catalytic pyrolysis of poplar wood. The metal oxides, especially TiO2 and NiO could suppress further cracking of primary products, increasing the tar yield and simultaneously decreasing the gas yield. The V, Mn, Ti or Co-based catalyst promoted the formation of the heavy bio-oil, while the Ce, Cr, Cu or Fe-based catalysts were the opposite. The metal oxides (except Fe2 O3 ) promoted the formation of alcohols, furan, ketones, acetic acid and phenolics in bio-oil. Fe2 O3 catalysts suppressed formation of the derivatives from cellulose and hemicellulose except hydroxyl acetone. Hydroxyl acetone formation was promoted by almost all the oxide catalysts while hydroxyl aldehyde formation was the opposite. Remarkable coke formed over the V, Mn, Cu and Co-based catalysts. These oxides contain multiple valences and could be partially reduced to generate oxygen vacancies, which played important roles in the polymerisation reactions. In addition, the coke species formed on the oxide catalysts were mainly polymeric with low thermal stability. Highlights: The metal oxides could increase tar yield and simultaneously decrease gas yield. V, Mn, Ti or Co oxides promoted heavy oil formation, Ce, Cr, Cu or Fe oxides didn't. Most metal oxides promoted alcohols, furan, ketones, acids and phenolics formation. Remarkable coke formed over the V, Mn, Cu and Co-based catalysts. The multiple valences and oxygen vacancies in oxides probably related to coking.